2019
DOI: 10.1016/j.biomaterials.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

An on-chip model of protein paracellular and transcellular permeability in the microcirculation

Abstract: Recent therapeutic success of large-molecule biologics has led to intense interest in assays to measure with precision their transport across the vascular endothelium and into the target tissue. Most current in vitro endothelial models show unrealistically large permeability coefficients due to a non-physiological paracellular transport. Thus, more advanced systems are required to better recapitulate and discern the important contribution of transcellular transport (transcytosis), particularly of pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
151
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 82 publications
(175 citation statements)
references
References 43 publications
16
151
2
Order By: Relevance
“…Previous authors also reported one order of magnitude lower permeability values in a 3D model compared with a 2D transwell model. [ 51 ] In the 3D in vitro model, transcytosis possibly played a more important role compared to paracellular transport. Conversely, in the 2D transwell set‐up, transcytosis effects were possibly inferior and paracellular transport prevailed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors also reported one order of magnitude lower permeability values in a 3D model compared with a 2D transwell model. [ 51 ] In the 3D in vitro model, transcytosis possibly played a more important role compared to paracellular transport. Conversely, in the 2D transwell set‐up, transcytosis effects were possibly inferior and paracellular transport prevailed.…”
Section: Discussionmentioning
confidence: 99%
“…The above‐described measurements were derived based on the 3D analysis of the confocal image stacks of the microvasculature as previously described. [ 51 ]…”
Section: Methodsmentioning
confidence: 99%
“…[27] Following stabilization (≈2-3 min), time-lapse confocal volumes were captured (3 × 5 min intervals). At day 7, devices were perfused with 10 kDa anionic Cascade-blue dextran (ThermoFisher) by a temporary drop in pressure across the gel region (complete removal of media followed by introduction of 40 µL of fluorescent solute into one channel).…”
Section: Methodsmentioning
confidence: 99%
“…[23,24] Consistent with their importance in vessel function, our group and others have shown that fibroblasts and pericytes are necessary for the maintenance and long-term growth of in vitro 3D microvessels. [21,26] After design and fabrication of the devices (see [27] for details), we set out to establish successful 3D in vitro microvessel generation in the presence or absence of human placental pericytes (HPPs). Using similar microscale devices, we have shown that microvessel formation occurs in a process akin to vasculogenesis (neo-vessel formation) within 1 week and allows for morphological and functional studies of human microvasculature.…”
Section: Placental Pericytes Inhibit Microvascular Growthmentioning
confidence: 99%
“…Therefore, in order to assess relevant TC extravasation 27 mechanisms, advanced experimental systems are required to recapitulate human physiology while 28 allowing for high spatiotemporal resolution imaging of cell interactions 14,25,26 . Our research group has 29 developed and used perfusable microvascular networks (MVNs) self-assembled from human ECs and 30 stromal cells within microfluidic devices 27 , which have been employed in the past to explore the role 31 of specific adhesion molecules, such as integrins, expressed on TCs 28 . The MVNs possess 32 morphological similarities to the human microvasculature in vivo and express a functional GCX 29 .…”
Section: Introductionmentioning
confidence: 99%